2023
DOI: 10.1108/edi-07-2022-0172
|View full text |Cite
|
Sign up to set email alerts
|

The impact of board-level female directors on firm performance: evidence from India

Abstract: PurposeThis study investigates the impact of female directors on firms' financial performance by scrutinizing the different roles they are empowered to fulfill.Design/methodology/approachThis study examines the impact of the roles performed by female directors on firms' financial performance using a panel dataset of the top 100 listed Indian firms over a period of 5 years. The study uses an appropriate panel data model for empirical analysis. For the robustness evaluation, a two-stage least square (2SLS) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…By reporting the correlation matrix for the explained and explanatory variables, Table 3 confirms that the studied variables included in the model are proper, as they are not highly correlated. Consequently, the issue of multicollinearity did not pose a significant worry in the examination of correlations since none of the explanatory variables had coefficients above the threshold of 0.700 (Mansour et al, 2024;Saha et al, 2023). The correlation coefficient in Table 3 highlights the interplay between the market performance of the banking sector, board gender diversity, and relevant control variables.…”
Section: Correlation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…By reporting the correlation matrix for the explained and explanatory variables, Table 3 confirms that the studied variables included in the model are proper, as they are not highly correlated. Consequently, the issue of multicollinearity did not pose a significant worry in the examination of correlations since none of the explanatory variables had coefficients above the threshold of 0.700 (Mansour et al, 2024;Saha et al, 2023). The correlation coefficient in Table 3 highlights the interplay between the market performance of the banking sector, board gender diversity, and relevant control variables.…”
Section: Correlation Analysismentioning
confidence: 99%
“…This study builds upon recent studies(Arora & Soni, 2023;Gharbi & Othmani, 2023;Marei, 2023) by relying on Tobin's Q as a market-based metric(Mansour et al, 2022b;Saha et al, 2023). It is calculated by adding the market value of stocks to the book value of debt and dividing it by the book value of total assets.…”
mentioning
confidence: 99%
“…It is the later class of non-executivesaccording to Harjoto et al (2018) that incite board watchfulness for corporate common good. Saha (2023) posits that the presence of INEDs mitigates agency dilemma because they are primarily responsible for executive monitoring and control. Liao et al (2015) reported that the presence of independent non-executive directors engenders attainment of financial and non-financial stability as well as reduced conflicts in stakeholders' expectations.…”
Section: H2 Gender-based Diversity Of Power Separation Impairs the Re...mentioning
confidence: 99%
“…It is important to note that empirical evidence from the Nigerian corporate environment would offer watertight validation for gender diversity in view of the 2022 Gender Gap Assessment report issued by the International Finance Corporation (IFC), which showed that women constituted 20 per cent of executive teams in Nigeriahigher than the global average (see Casanova et al, 2022). Secondly, the paper is inspired by the need to de-emphasise research linking board gender diversity to overall corporate performancewhich most often presents ambiguous outcomes (Chatterjee & Nag, 2023;Saha, 2023;Simionescu et al, 2021;Nielsen & Huse, 2010). The paper offers a role-based approach with emphasis on how gender disparity among directors affects the effectiveness of boards' role in facilitating achievement of specific corporate common good such as foreign capital importation.…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu, hasil ini juga menunjukkan bahwa direktur eksekutif perempuan dalam konteks India tidak mampu menyelesaikan masalah keagenan horizontal antara pemegang saham mayoritas dan minoritas karena mereka umumnya mewakili kelompok sebelumnya. Dengan demikian, dapat disimpulkan bahwa direktur perempuan independen secara khusus berkontribusi pada dampak keseluruhan kuota gender dewan terhadap kinerja perusahaan Saha, 2023).…”
Section: Studi Kasus DI Indiaunclassified